Pengaruh Model Kooperatif Tipe Course Review Horay Pada Hasil Belajar Siswa Mata Pelajaran IPS Kelas VI SD Negeri 13 Pasar Kambang - Winda Anjelina; Firman Firman; Desyandri Desyandri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This study was to see whether there was an effect of the CRH-type cooperative model on social studies learning outcomes in grade VI SD. This type of research is "posttest-only control design". Learning outcomes observed in the cognitive domain were seen from the results of the final learning test. Where the experimental class with an average of 80.2, the control class 70.77. In the statistical test the price of tcount> ttable (0.05; 49) (2.091> 2.011) with a level (α = 0.05), the H1 hypothesis is accepted. The conclusion is that the CRH type cooperative model has an effect on learning outcomes in Social Sciences subjects. Thus the CRH type cooperative model is suitable to be used to assist teachers in the learning process in schools.